(untitled) (Development Service Industry Management, 2025)
As the popularity of home-sharing services grows among tourists, traditional accommodation methods are facing increased competition. The competitive advantage of short-term rentals is that much of this sector is in the informal economy and largely does not pay taxes, whereas the hotel industry is forced to do so. Such realities make this business model successful and more competitive than traditional hotel business models. According to the European Commission, the short-term rental segment accounts for more than 23% of the tourist accommodation sector and is growing rapidly. Due to the growing competition from short-term rentals, there is a threat of declining revenues for hotel businesses. This situation requires an increase in the efficiency of hotel yield management, which, accordingly, involves improving the quality of analytical support for managers. The article investigates the competitive environment in the sphere of temporary accommodation of tourists; it assesses the positioning of hotels among other means of collective accommodation; it studies the foreign experience of using analytical tools to justify the decisions of hotel managers. Given the high level of informal economy of the hospitality industry in Ukraine and, accordingly, significant competition in the sector of temporary accommodation of tourists, we believe it is advisable in the practice of analytical work of domestic managers of hotel business to determine the KPI of yield management, which are used in foreign practice, and to conduct a factor analysis of these indicators using traditional methods of economic analysis. The results of such analyses will allow hotel managers to make informed decisions in order to increase revenues from the room stock operation.